Third-stage larvae of the enoplid nematode Dioctophyme renale (Goeze, 1782) in the freshwater turtle Trachemys dorbigni from southern Brazil. Issue 5 (September 2015) - Mascarenhas, C.S.; Müller, G.
Abstract The giant kidney worm Dioctophymerenale is normally found in wild carnivores and domestic dogs, with aquatic oligochaetes acting as intermediate hosts. In the present study a prevalence of 50% of third-stage larvae of D. renale was recorded in 60 specimens of the freshwater turtle Trachemys dorbigni from southern Brazil. Larvae were encysted in muscles, the coelomic cavity and mesentery, the serous lining of the stomach and on the surfaces of the lung, heart, liver, pancreas, spleen and intestines. There are no previous records of reptiles being part of the life cycle of D. renale, although fish and amphibians normally act as paratenic hosts. This is the first report of third-stage D. renale larvae in the freshwater turtle, T. dorbigni.